Normative Evolution in Europe: Small States and Republican Peace - Kostas A. Lavdas (London School of Economics and Political Science (LSE), European Institute, 2010)
Understanding today's EU requires a prism which is attentive to the interactions between the polity-building and world-inhabiting facets of the emerging polity. We cannot separate developing a theory of the EU as a polity from determining its placement in the world. Norms of cooperation become crucial in this endeavour: as they search for credible tools to interpret and master a changing Europe in a changing world, actors distil their experience in close and repeated cooperation with a view to enhancing their knowledge of and influence over complex games of advanced hyper-dependence. The normative underpinnings of today's European construction can be approached in three steps. First, drawing inspiration from Thucydides, we demonstrate that the norms that count are neither religious in origin nor based primarily on custom and tradition. Next, we point to the significance of small states in norm development by explaining that the norms in question have been influenced by the practices and rationalizations associated with small-states behaviour, adaptability and survival. Finally, we suggest that the norms in question have evolved in interaction with a powerful current in Euro-Atlantic political thought and sensibility: republicanism. The paper identifies two main sets of norms in today's EU: one stemming from previous experiences within the international system and the other developing with the new polity-in-the-making.
Keywords: 330